Takeover of Daraz Bangladesh by Alibaba Group and change in vendor acquisition process at Daraz Bangladesh - Dipta, Md Shakir Uddin (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.